Paediatric acute care: Highlights from the PAC‐APLS conference, Sydney, 2015. (22nd June 2016) - Teo, Stephen; Stanford, Jane; Rao, Arjun; Babl, Franz E
Abstract: The Paediatric Acute Care Conference (PACC) is an annual conference organised by Advanced Paediatric Life Support (APLS) Australia to advance paediatric acute care topics for clinicians in pre‐hospital medicine, EDs, acute paediatrics, intensive care and anaesthesia. All PACC content is made available free online (https://vimeo.com/aplsaustralia ). The PAC conference 2015 was held at Coogee, Sydney. We provide a summary of some of the presentations.